Cooperation in Wireless Networks: Principles and Applications Real Egoistic Behavior is to Cooperate! - Fitzek, Frank H. P.; Katz, Marcos D. (Springer Netherlands : Imprint: Springer, 2006)
Cooperation in Wireless Networks: Principles and Applications covers the underlying principles of cooperative techniques as well as several applications demonstrating the use of such techniques in practical systems. The work is written in a collaborative manner by several authors from Asia, America, and Europe. Twenty chapters introduce and discuss in detail the main cooperative strategies for the whole communication protocol stack from the application layer down to the physical layer. Furthermore power saving strategies, security, hardware realization, and user scenarios for cooperative communication systems are introduced and discussed. The book also summarizes the strength of cooperation for upcoming generation of wireless communication systems, clearly motivating the use of cooperative techniques and pointing out that cooperation will become one of the key technologies enabling 4G and beyond. This book puts into one volume a comprehensive and technically rich view of the wireless communications scene from a cooperation point of view.